The Phylogeny and Pathogenesis of Sacbrood Virus (SBV) Infection in European Honey Bees, Apis mellifera - Li, Jianghong; Wang, Tingyun; Evans, Jay; Rose, Robyn; Zhao, Yazhou; Li, Zhiguo; Li, Jilian; Huang, Shaokang; Heerman, Matthew; Rodríguez-García, Cristina; Banmeke, Olubukola; Brister, J.; et al. (Viruses, 2019)
RNA viruses that contain single-stranded RNA genomes of positive sense make up the largest group of pathogens infecting honey bees. Sacbrood virus (SBV) is one of the most widely distributed honey bee viruses and infects the larvae of honey bees, resulting in failure to pupate and death. Among all of the viruses infecting honey bees, SBV has the greatest number of complete genomes isolated from both European honey bees Apis mellifera and Asian honey bees A. cerana worldwide. To enhance our understanding of the evolution and pathogenicity of SBV, in this study, we present the first report of whole genome sequences of two U.S. strains of SBV. The complete genome sequences of the two U.S. SBV strains were deposited in GenBank under accession numbers: MG545286.1 and MG545287.1. Both SBV strains show the typical genomic features of the Iflaviridae family. The phylogenetic analysis of the single polyprotein coding region of the U.S. strains, and other GenBank SBV submissions revealed that SBV strains split into two distinct lineages, possibly reflecting host affiliation. The phylogenetic analysis based on the 5′UTR revealed a monophyletic clade with the deep parts of the tree occupied by SBV strains from both A. cerane and A. mellifera, and the tips of branches of the tree occupied by SBV strains from A. mellifera. The study of the cold stress on the pathogenesis of the SBV infection showed that cold stress could have profound effects on sacbrood disease severity manifested by increased mortality of infected larvae. This result suggests that the high prevalence of sacbrood disease in early spring may be due to the fluctuating temperatures during the season. This study will contribute to a better understanding of the evolution and pathogenesis of SBV infection in honey bees, and have important epidemiological relevance.